Impact of using corrugated wall and nanofluid on the performance improvement of thermoelectric generator mounted channels - Hessem Djeddou; Brahim Fersadou; Henda Kahalerras; Mohamed Benelhaoues (Revue des Énergies Renouvelables, 2025)
The influence of using a corrugated wall as a passive heat transfer enhancement technique for the sake of improving the power generation of thermoelectric generator (TEG) located in between two corrugated channels flowing nanofluid has been numerically examined. The upper and the lower channels carry hot and cold water-based single-walled carbon nanotube nanofluid (SWCNT), respectively. Finite element method, FEM, is chosen to tackle the 3D steady-state equations governing the TEG with associated boundary conditions. Several parameters related to the performance of thermoelectric generator such as Reynolds number (between 50 and 1000) and the number of corrugations (between 1 and 5) were in depth assessed. The findings indicate that the Reynolds number plays a significant role in improving thermoelectric power generation. When the Reynolds number increases, TEG produces a higher electric power value. However, the results also reveal that the number of corrugations has a limited impact on the performance of TEG.